PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI KALIMANTAN BARAT - B11109050, AGUNG YUDIKA (Jurnal Manajemen Update, 2014)
This research was titled "The Effect of Emotional Intelligence on Performance of Civil Servants Department of Education and Culture of West Kalimantan". The purpose of this research is to know the influence of emotional intelligence on the performance of civil servants Department of Education and Culture of West Kalimantan. The method used in this study is causal research method is a method of research that indicates the causal direction between the independent variables and the dependent variable to measure the strength of the relationship between variables. The samples in this research is the civil servants Department of Education and Culture of West Kalimantan with a total of 60 people. The data collection method is to use a questionnaire. Analysis technique using multiple linear regression analysis. Based on the results of the research that has been done that the five indicators of emotional intelligence have a significant effect on the performance of employees simultaneously with a probability value (p) of F value of 0.001 and 4.734. However, the five indicators of emotional intelligence has no significant influence on the performance of employees partially with p> 0.05. Keywords: emotional intelligence, employee performance